The thermal catalytic effects of CoFe-Layered double hydroxide derivative on the molecular perovskite energetic material (DAP-4). (November 2021) - Fang, Hua; Guo, Xueyong; Wang, Wei; Nie, Jianxin; Han, Kehua; Wu, Chengcheng; Wang, Shuji; Wang, Di; Deng, Peng
Abstract: The application of nano-catalytic materials in molecular perovskite energetic materials is of great significance to promote the development of molecular perovskite energetic materials in explosive formulations and propellants. In this paper, the thermal catalytic effects of CoFe-layered double hydroxide derivative on the molecular perovskite energetic material (DAP-4) were studied. In this study, we successfully prepared a new type of CoFe-based photothermal agent (CoFe-500) by heating CoFe layered double hydroxide nanosheets in an Ar atmosphere at 500 °C. And the micromorphology, structure composition, thermal decomposition performances of CoFe-500 and DAP-4/CoFe-500 composite were characterized. The experimental results showed that with the addition of CoFe-500, the initial decomposition temperature and peak exothermic temperature of DAP-4 showed a decreasing trend. With 10 wt% CoFe-500 added, the initial decomposition temperature and peak exothermic temperature of DAP-4 decreased from 305.6 °C to 166.3 °C and 379.0 °C–322.5 °C, respectively (10 °C/min heating rate). The apparent activation energy ( E a ) of pure DAP-4 is 172.27 kJ/mol and 175.13 kJ/mol calculated by the Kissinger and Ozawa method, respectively. And with 10 wt% CoFe-500 added, the E a is reduced to 119.11 kJ/mol and 122.84 kJ/mol, respectively. The possible thermal catalytic decomposition mechanism of DAP-4/CoFe-500 composites was proposed from the thermal analysis and mass spectrometry test results. This work is meaningful to further understand the decomposition performances of DAP-4 in the presence of nano-layered double hydroxide. Highlights: The thermal catalytic effects of CoFe-layered double hydroxide derivative on the DAP-4 were studied for the first time. The initial decomposition temperature and  T p  of DAP-4 showed a decreasing trend with the increase of CoFe-500 content. A possible thermal decomposition mechanism of DAP-4 catalyzed by CoFe-500 was proposed.